The effects of cuban oregano (Plectranthus amboinicus) powder on the quality of fish balls - Saldaña, Carinna T. (2013.)
Antioxidant and antimicrobial property of herbs and spices have been known since antiquity.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Oregano